Representing Scotland: Conservative narratives of nation, union, and Scottish independence - Brown Swan, Coree; Anderson, Paul (Frontiers in Political Science, 2024)
The United Kingdom's vote to exit the European Union reignited the debate about Scottish independence, requiring statewide political parties to rearticulate the case for the Union. The UK Conservative Party, as the party of government and one with a tumultuous history vis-àvis Scotland and devolution, was at the fore in making this case. This article explores representations of Scotland, its position within the United Kingdom, and Scottish nationalism as a political force by the Conservative Party at a prolonged moment of significant political and constitutional tension. We focus, therefore, on 2019 to 2024, a parliamentary term and political period defined by protracted debates on Scotland's place within the Union, playing out against the backdrop of the Brexit negotiations, the Covid-19 pandemic, and a worsening cost-of-living crisis. To this end, we draw upon parliamentary debates, two daily English newspapers (The Daily Telegraph and the Sun) and two online right-leaning news sites (ConservativeHome and The Spectator online). Our analysis identifies three distinct but interrelated strands in Conservative representations of Scotland, each of which is centred on a contrast. First, a distinction between an inclusive unionism versus a narrow nationalism; second, a largely economic narrative, contrasting a prosperous union with the economic risks of independence; and finally, a contrast between governmental competence at Westminster and the SNP-led Scottish Government failing Scotland. These contrasting narratives elucidate the ways in which Conservatives construct representations of Scotland, particularly at moments of constitutional contestation.